Theory of motion of grain mixture particle in the process of aspiration separation - Bulgakov, Volodymyr; Nikolaenko, S.; Holovach, I.; Boris, A.; Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Olt, J. (My University, 2020)
The paper describes the development of a mathematical model for the motion of a seed mixture particle in the aspiration channel of the separator after the particle passes the cone-shaped spreader and enters the workspace of the aspiration channel in the pneumatic dynamics and vibration unit devised by the authors. The unique feature of the proposed new design is the presence of the central pipe with sail members in the aspiration channel. The sail members in the air stream generate the self-oscillatory mode of motion of the central pipe, which results in the efficient separation of the grain seed mixture into the required fractions. On the basis of the prepared equivalent schematic model, the differential equations of the motion of a seed mixture particle in the process of aspiration separation have been generated. Basing on the results of the PC-assisted numerical modelling of the motion paths, on which the material particles (seeds) of the heavy and medium fractions travel, it has been established that they move on different courses, and the course of the heavy fraction seeds is such that, after they pass the cone-shaped spreader and advance further in the air stream through the space of the aspiration channel, they move closer to the pipe of the aspiration channel. Also, their velocities and accelerations are greater than the same kinematic parameters of the medium fraction seeds. The seeds of the light fraction move upwards under the action of the air stream and leave the aspiration separator at its top.
Keywords: air flow; aspiration channel; grain seed mixture; material particle; separation